A new genus and two new species of chigger mites (Trombidiformes: Leeuwenhoekiidae) from Brazilian caves with notes about the genus Whartonia Ewing, 1944 - Bassini-Silva, R. [UNESP]; Zampaulo, R. A.; Welbourn, C.; Ochoa, R.; Brescovit, A. D.; Barros-Battesti, D. M. [UNESP]; Jacinavicius, F. C. (Taylor & Francis, 2022)
The family Leeuwenhoekiidae has a worldwide distribution. In Brazil, it is represented by five genera and 10 species parasitising all groups of terrestrial vertebrates. Examination of material housed in the Acari Collection of the Instituto Butantan revealed undescribed species belonging to this family. In the present study, we describe a new genus, Caramuruacarus gen. nov., with the type species Caramuruacarus carnavalesca sp. nov. from the Minas Gerais State and a new species for the genus Whartonia, Whartonia parauapebensis sp. nov., from Pará State, both from the soil of Brazilian caves. In addition, a discussion of the genus Whartonia and its subgenera is provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:B4D09A27-D163-4772-B4FA-79949D5FEC9F http://www.zoobank.org/urn:lsid:zoobank.org:pub:F3533B72-8643-467F-A348-63534EB67AAA http://www.zoobank.org/urn:lsid:zoobank.org:pub:3BC85F16-1E6D-4FFB-9B71-465A2689D9EE.
Keywords: Acari; caves; chigger; ectoparasite; new genus; new species